Antenatal Exposure to Magnesium Sulfate and Spontaneous Intestinal Perforation and Necrotizing Enterocolitis in Extremely Preterm Neonates - Shalabi, Mohamed; Mohamed, Adel; Lemyre, Brigitte; Aziz, Khalid; Faucher, Daniel; Shah, Prakesh S.; for the Canadian Neonatal Network Investigators (American Journal of Perinatology, 2017)
Background There have been recent concerns regarding the higher rates of spontaneous intestinal perforation (SIP) in preterm infants that have been exposed to intrapartum magnesium sulfate (MgSO4).Objective To assess the association between intrapartum MgSO4 exposure and necrotizing enterocolitis (NEC) and/or SIP in extremely preterm neonates.Design A retrospective cohort study was conducted using data from the Canadian Neonatal Network database. Infants born at < 28 weeks' gestation admitted to neonatal units in Canada between 2011 and 2014 were divided into two groups: those exposed antenatally to MgSO4 and those unexposed. Stratified analyses for infants born between 22 and 25 weeks' gestation and those born between 26 and 27 weeks' gestation were conducted. The primary outcome was intestinal injury, identified as either NEC or SIP. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were calculated using multivariable logistic regression.Results We compared 2,300 unexposed infants with 2,055 exposed infants. There was no difference in the odds of NEC (9.88% exposed vs. 9.59% unexposed; aOR: 0.92; 95% CI: 0.75–1.14) or SIP (3.4% exposed vs. 3.39% unexposed; aOR: 1.05; 95% CI: 0.75–1.48) between the two groups.Conclusion Antenatal exposure to MgSO4 was not associated with NEC or SIP in extremely preterm infants.
Keywords: magnesium sulfate; spontaneous intestinal perforation; necrotizing enterocolitis; preterm infants